Dictators, democracy, and American public culture : envisioning the totalitarian enemy, 1920s-1950s - Alpers, Benjamin Leontief, 1965- (Cultural studies of the United States., 2003)
Focusing on portrayals of European dictatorships in US films, magazine and newspaper articles, books, plays, speeches and other texts, this study traces changing American understandings of dictatorship from the late 1920s through to the early years of the Cold War.